Numinous Poiesis in Pentecostal Music: Jubilant Chants, Enjoyment of Enlivening and Dances in the Fire of the Spirit (Universidad de Chile. Facultad de Artes, 2012)
In this paper the role of music as generator of the religious experience among members of the Pentecostal group is analyzed. The importance of music in the charismatic evangelistic rhetoric is studied along with its support for the performing structure of the cult as an element of continuity and a characteristic feature of its evolution. The different functions of music are examined putting an emphasis on its role as means of enlivening the congregation to bring out the Holy Spirit. Due to the capacity of music for social and somatic synchronization, choral performance by the congregation creates a transpersonal experience preceding processes of emotional changes and inducing deep bodily states of conscience in dance, which are considered as supernatural signs of power Music appears here as a powerful vehicle for transcending the daily world of life with cathartic and strengthening effects.